Electrically Reconfigurable Phase-Change Transmissive Metasurface - Popescu, Cosmin Constantin (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH. This article has been contributed to by U.S. Government employees and their work is in the public domain in the USA.